An Engineered β‐Hairpin Peptide Forming Thermostable Complexes with ZnII, NiII, and CuII through a His3 Site. (16th December 2022) - Pham, Truc Lam; Fazliev, Sunnatullo; Baur, Philipp; Comba, Peter; Thomas, Franziska
Abstract: The three‐dimensional structure of a peptide, which determines its function, can denature at elevated temperatures, in the presence of chaotropic reagents, or in organic solvents. These factors limit the applicability of peptides. Herein, we present an engineered β‐hairpin peptide containing a His3 site that forms complexes with Zn II, Ni II, and Cu II . Circular dichroism spectroscopy shows that the peptide−metal complexes exhibit melting temperatures up to 80 °C and remain folded in 6 M guanidine hydrochloride as well as in organic solvents. Intrinsic fluorescence titration experiments were used to determine the dissociation constants of metal binding in the nano‐ to sub‐nanomolar range. The coordination geometry of the peptide−Cu II complex was studied by EPR spectroscopy, and a distorted square planar coordination geometry with weak interactions to axial ligands was revealed. Due to their impressive stability, the presented peptide−metal complexes open up interesting fields of application, such as the development of a new class of peptide−metal catalysts for stereoselective organic synthesis or the directed design of extremophilic β‐sheet peptides. Abstract : Braving the extremes : A small metal‐binding and thermostable β‐sheet peptide based on a tryptophan zipper has been designed. The resulting peptide−metal complex resists high temperatures, chaotropic reagents and organic solvents. These properties are not only interesting from a biophysical point of view, but also show the potential for future use of the peptide as a ligand in metal‐catalysed organic reactions.